Development of hydrological cycle learning media based on android application for fifth grade elementary school students - Safitri, Dhea Rahma; Cahyadi, Fajar; Ardiyanto, Asep (Jurnal Bidang Pendidikan Dasar, 2024)
Many teachers only focus on using books so that students feel bored and bored with learning, which results in learning not being maximally received. Educational media is used as a tool in learning activities to assist teachers and students in achieving learning goals, where technology has become an integral part of all activities. This study aims to develop multimedia learning applications for hydrology subjects for grade v elementary school students. The methodology used is R&D, focusing on the development process. The application is made through the analysis, design, and development stages. Validation from two validators of the media gave 94% results and stated the validity of the media without revision to be used in learning the hydrological cycle in the school curriculum. recommendations from this study are to improve user identity features and quiz features in the surrounding environment.